Advances in Microclimate Ecology Arising from Remote Sensing. (April 2019) - Zellweger, Florian; De Frenne, Pieter; Lenoir, Jonathan; Rocchini, Duccio; Coomes, David
Abstract : Microclimates at the land–air interface affect the physiological functioning of organisms which, in turn, influences the structure, composition, and functioning of ecosystems. We review how remote sensing technologies that deliver detailed data about the structure and thermal composition of environments are improving the assessment of microclimate over space and time. Mapping landscape-level heterogeneity of microclimate advances our ability to study how organisms respond to climate variation, which has important implications for understanding climate-change impacts on biodiversity and ecosystems. Interpolating in situ microclimate measurements and downscaling macroclimate provides an organism-centered perspective for studying climate–species interactions and species distribution dynamics. We envisage that mapping of microclimate will soon become commonplace, enabling more reliable predictions of species and ecosystem responses to global change. Highlights: Microclimates are often neglected in ecology and evolution, despite mounting evidence that microclimates matter for ecosystem dynamics and processes, such as the response of organisms to climate change. Remote sensing approaches to measure the 3D structure and thermal composition of terrestrial ecosystems significantly advance microclimate modeling and mapping. This provides novel opportunities for fundamental and applied microclimate ecology, forestry, and agriculture. Increased efforts to use remote sensing to upscale in situ microclimatic measurements will further our mechanistic understanding of how topography and vegetation structure determine microclimate. Detailed spatial and temporal microclimate data derived from remote sensing may lead to more realistic predictions of microclimate and the associated biotic responses to global change.